The Effects of Economic Consumption: The Nexus between Macroeconomic Drivers and Financial Development - Upadhyaya, Yadav Mani; Kharel, Khom Raj; Budhathoki, Dhruba Kumar (Dhaulagiri Journal of Sociology and Anthropology, 2025)
This study investigates the economic consumption of Nepal, focusing on the roles of remittances, financial development, inflation, and income. The aim is to assess both short-term and long-term relationships and provide policy insights. The research employs the Autoregressive Distributed Lag (ARDL) bounds testing approach to analyze time-series data spanning from 1975 to 2023. Data were sourced from the Ministry of Finance, Nepal Rastra Bank, and World Bank databases. Key variables include remittances, Gross Domestic Product (GDP) per capita, consumer price indices, urban population, and private credit. Diagnostic tests ensured the model’s reliability and stability. The findings reveal significant influences of remittances on private consumption, with urban population growth exhibiting a strong positive short-term effect. Remittances initially have a negative impact on consumption but display significant long-term benefits. Inflation shows a short-term stimulatory effect on consumption, while financial development (proxied by private credit) demonstrates a delayed negative impact. Cointegration tests confirm a highly significant error correction term (-1.49), indicating long-term equilibrium and an effective adjustment mechanism, with deviations corrected within approximately 8 months (0.67 years). Private consumption in Nepal is shaped by a dynamic interplay of socio-economic factors. Urbanization and remittance inflows are key drivers, emphasizing the need for policies fostering urban planning and remittance management. Addressing inflationary pressures and enhancing financial inclusion could further optimize economic consumption, contributing to sustained economic growth and stability.